2021
DOI: 10.1007/s10064-021-02157-x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on the poroelastic response of a water-saturated limestone to hydrostatic compression

Abstract: This contribution addresses an experimental study on the poroelastic behavior of a water-saturated limestone. Samples come from Sarvak limestone, a major hydrocarbon-producing reservoir in Iran. Three back-saturated intact specimens were subjected to hydrostatic compression with different boundary pressure conditions. A coherent workflow from testing to data interpretation was established to efficiently deal with possible sources of uncertainty and provide accurate results. Obtained results revealed that drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The coefficient of proportionality, ranging from 0 to 1, is also called the Skempton's coefficient α with a value of 0.5 (P o = αP c). This value is low compared to what is found in laboratory measurements (Ahmadinejad & Kivi, 2021), but is still realistic in an in-situ context (Roeloffs, 1996). Doetsch et al (2018) observed that seismic velocity changes (dv/v) were proportional to effective pressure P e = P c − P o, where P o is pore pressure.…”
Section: Results and Interpretationmentioning
confidence: 60%
“…The coefficient of proportionality, ranging from 0 to 1, is also called the Skempton's coefficient α with a value of 0.5 (P o = αP c). This value is low compared to what is found in laboratory measurements (Ahmadinejad & Kivi, 2021), but is still realistic in an in-situ context (Roeloffs, 1996). Doetsch et al (2018) observed that seismic velocity changes (dv/v) were proportional to effective pressure P e = P c − P o, where P o is pore pressure.…”
Section: Results and Interpretationmentioning
confidence: 60%